Psychometric properties of the Icelandic version of Worry Behaviours Inventory (WBI) in clinical and non-clinical samples - Ásta Sigurðardóttir 1983- (2019)
Generalized anxiety disorder (GAD) is the only anxiety disorder to date in the DSM-5 and ICD-10 where behavioural avoidance is not included in the diagnostic criterion. However, studies suggest that individuals with GAD engage in various maladaptive behaviours. This study aimed to assess the psychometric properties of the Icelandic version of the Worry Behaviour Inventory (WBI) in a clinical- and non-clinical sample. The WBI is a self-report measure designed to identify maladaptive behaviours that have been associated with GAD. Participants consisted of 256 students at Reykjavík University and 21 patients diagnosed with GAD as a primary or secondary diagnosis. Participants completed measures of worry related behaviour (WBI), anxiety symptoms (GAD-7), depression (PHQ-9), worry (PSWQ), social anxiety (SPS), intolerance of uncertainty (IUS-B) and symptoms of GAD (WAQ). Exploratory factor analysis indicated a two factor solution. The internal reliability of the WBI was good (Cronbach’s α = .87) in the non-clinical sample and adequate (Cronbach’s α = .77) in the clinical sample. The results supports the convergent and discriminant validity of the scale. The WBI predicted worry over and above measures of anxiety, depression and intolerance of uncertainty, supporting incremental validity of the scale. The WBI discriminated between the non-clinical and clinical samples. Preliminary results support the reliability and validity of the WBI in a non-clinical sample. The WBI may enable clinicians to identify behaviours that are theorized to maintain GAD and can be targeted during psychological treatment. Keywords: generalized anxiety disorder, safety-seeking behaviour, psychometric properties